Bloom's Taxonomy Approach to Cognitive Space Using Classic Test Theory and Modern Theory - Helvy Yunida; Riyan Arthur (East Asian Journal of Multidisciplinary Research, 2023)
Bloom's Taxonomy is an operational verb (KKO) developed by Benyamin S. Bloom, with the aim of developing education which includes cognitive, affective and psychomotor aspects. The aim of this research is Bloom's Taxonomy Approach To Cognitive Space Using Classic Test Theory And Modern Theory. KKO is needed by a teacher, lecturer or facilitator or trainer to make a syllabus and Learning Implementation Plan (RPP). The Classical Theory Test is one of the test models that is still quite useful today which is still used in research to describe an error in measurement that can affect the observed score. This classical test theory is also an attempt to explain errors in a measurement. While the modern theory test is called the system analysis theory or open theory which combines classical and neoclassical theory. Modern organizational theory sees that all elements of an organization are interdependent and inseparable. The research method uses literature review, namely by collecting data techniques looking for materials from journals, books and from the internet (google, google scholar) and others. The results of the research show that data processing uses classical theory tests and modern theories, variations and modifications are obtained that can develop knowledge in the research field.